COLLABORATIVE LEARNING VIA SHARING SESSION TOWARDS ACHIEVING TRAINING EFFECTIVENESS IN NEGOTIATION EDUCATION (Journal of Technology and Operations Management, 2016)
Attaining training effectiveness for Negotiation as an elective subject in obtaining Bachelor of Human Resource Management in University Utara Malaysia will be beneficial for students when they start to work. The subject requires strong fundamental knowledge in human resource management and other management related subjects, as it demands students to be able to relate issues and needs in business venture strategic decision. However, the drawback in achieving this is difficult because students are weak in the basics due to low clasp of fundamental understanding. This action research has been conducted in two consecutive semesters in order to find the best way to improve student basic understanding thus connection to the higher-level knowledge is possible. The objective of this study is to evaluate collaborative learning as stipulated in the Theory of Planned Behaviour where we focus on the relationship between the intention to transfer training and training effectiveness. The method used is by introducing a sharing session, through small group discussion has been chosen for the purpose of developing effective negotiation education. As a result, students are more comfortable to be open-minded and less stressful while learning with their peers compared to instructors. Based on interviews and observations, results found that collaborative learning does improve understanding and built critical thinking. The approach developed has resulted in a more relaxed conducive learning environment and the training effectiveness achieved served as evidence in students’ performance.